The Role of Policy in Improving Student Literacy and Numeracy in the Era of the Merdeka Curriculum - Kartini, Eni; Darmawan, Deni; Omonovich, Khammataliev Dostnazar; Kibrio, Burieva (Journal of Innovation and Research in Primary Education, 2025)
This article examines the pivotal role of education policy in enhancing students' reading (literacy) and numeracy skills in the new era of the Merdeka Curriculum in Indonesia. Through a comprehensive review of various studies and educational literature, this article explores how current policies support schools and teachers in fostering these foundational skills among students. It identifies key challenges in policy implementation that may hinder its overall effectiveness. The findings suggest that effective education policy should grant schools the flexibility to tailor learning approaches to student needs while providing adequate support for teachers to develop engaging and developmentally appropriate literacy and numeracy programs. The article proposes several policy recommendations, including increased investment in teacher training, development of localized learning materials, and the integration of continuous assessment tools to monitor student progress. Furthermore, this study addresses specific research questions: (1) How do current education policies influence the development of literacy and numeracy in primary and secondary schools? (2) What are the main barriers faced by educators in implementing the Merdeka Curriculum effectively? and (3) What policy adjustments are needed to better align national education goals with classroom practices? This article aims to offer a clearer understanding of how education policies can contribute to shaping a more literate and numerate generation of Indonesian students.